2013
DOI: 10.1098/rsta.2012.0149
|View full text |Cite
|
Sign up to set email alerts
|

CRONE control system design toolbox for the control engineering community: tutorial and case study

Abstract: Fractional-order differentiation offers new degrees of freedom that simplify the design of high-performance dynamic controllers. The CRONE control system design (CSD) methodology proposes the design of robust controllers by using fractional-order operators. A software toolbox has been developed based on this methodology and is freely available for the international scientific and industrial communities. This paper presents both the CRONE CSD methodology and its implementation using the toolbox. The design of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…We present numerical simulations of the special solution of our model using the Adams-Moulton rule given by Equation (23) and Equations (49) and ( …”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations
“…We present numerical simulations of the special solution of our model using the Adams-Moulton rule given by Equation (23) and Equations (49) and ( …”
Section: Examplementioning
confidence: 99%
“…The vertical template is then replaced by a generalized template or by a multi-template (or curvilinear template) defined by a set of generalized templates. Here also, the transfer function is defined a posteriori based on the open-loop behavior [49].…”
Section: Crone Controllers Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that it is sufficient for ωl to be one decade less ωB, whereas for ωl, it must be one decade above ωh [49].…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the papers can be roughly grouped into three parts: three papers for fundamental theories of fractional calculus [7][8][9], five papers for fractional modelling with applications [10][11][12][13][14] and four papers for numerical approaches [15][16][17][18].…”
mentioning
confidence: 99%